PENINGKATKAN INOVASI PENELITIAN TINDAKAN KELAS GURU MELALUI PELATIHAN SOFTWARE STATISTIK SPSS DENGAN METODE ANOVA SATU JALUR - Dedek Andrian; Emkhad Arif; Nofriyandi Nofriyandi (LPPM Universitas Al Muslim, 2022)
Statistical ability is a skill that must be possessed by teachers as educators in every educational unit because statistics is useful for teachers to innovate in research. The lack of teacher ability in using statistical software makes teachers lack innovation in conducting research. This service aimed to provide the ability to use SPSS software to assist teachers in CAR research. The method used in this service activity including a workshop by giving training participants, namely all MGMP teachers (Assembly of Subject Teachers) in Pelawan Regency, Riau Province. This activity was carried out at SMPN 3 Sorek. The results of the service showed that all teachers were highly motivated to participate in the activity because they gained new knowledge for analyzing research data with SPSS. In addition, the teacher also knew that CAR data analysis can be carried out using a comparative method in the form of a T-test or ANOVA (analysis of variance), depending on several cycles in the study. The T test was used to compare cycles I and II, while ANOVA was used to compare cycles I, II and III.